2016
DOI: 10.1097/md.0000000000003145
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Like Liver Abscess Mimicking Malignancy With Lung Metastases in a Patient With Acute Renal Failure

Abstract: The worldwide incidence of Klebsiella pneumoniae liver abscess (KLA) is increasing. It is important to accurately diagnose this life-threatening disease to provide timely and appropriate treatment. Here we report the case of a 38-year-old man with acute renal failure and a tumor-like liver abscess and septic pulmonary embolism. Initially, his clinical symptoms, laboratory tests, and radiological findings presented equivocal results of malignancy with metastases. Fine needle aspiration of liver tumor was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In one case report, 19 multi‐dimensional CT was suggestive of metastatic liver lesions until it was confirmed as pyogenic liver abscesses by appearance of ultrasound‐guided aspirate of the largest lesion and its microbiology results. Similar case reports where lesions earlier thought to be malignant or metastatic lesions eventually diagnosed as pyogenic, 20 tubercular, 21 syphilitic, 22 toxocariasis, 23 amebic, 24 and actinomycosis 25 liver masses have been reported. Other case reports have cited initial infectious‐appearing liver lesions eventually being diagnosed as neoplastic lesions, 26‐28 including neuroendocrine tumor 29,30 …”
Section: Discussionsupporting
confidence: 69%
“…In one case report, 19 multi‐dimensional CT was suggestive of metastatic liver lesions until it was confirmed as pyogenic liver abscesses by appearance of ultrasound‐guided aspirate of the largest lesion and its microbiology results. Similar case reports where lesions earlier thought to be malignant or metastatic lesions eventually diagnosed as pyogenic, 20 tubercular, 21 syphilitic, 22 toxocariasis, 23 amebic, 24 and actinomycosis 25 liver masses have been reported. Other case reports have cited initial infectious‐appearing liver lesions eventually being diagnosed as neoplastic lesions, 26‐28 including neuroendocrine tumor 29,30 …”
Section: Discussionsupporting
confidence: 69%
“…Because this bacterium is considered an opportunistic pathogen arising from normal flora on snake skin, the mass was suspected to be an abscess [12,13]. Furthermore, after referring to human cases, we found that several reports have indicated that abscess-mimicking tumors and tumor-mimicking abscesses can cause confusion in differential diagnoses [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…HBV-ACLF is caused by spontaneous severe acute exacerbation in patients with CHB, which results in jaundice, coagulopathy or hepatic encephalopathy and sometimes liver failure, with high short-term (28 days) (>15%) and annual mortality rates(>50%) 1 31 . The importance of the diagnosis and prognosis for impending organ failure cannot be overemphasized in this particular group of patients, as a timely intervention can prevent or reverse the process and improve survival.…”
Section: Discussionmentioning
confidence: 99%